Anthropometric and physical fitness parameters versus specific performance tests in Brazilian field hockey athletes: a pilot study - Silva Lemos, R.; Andrade Paz, G.; de Freitas Maia, M.; Baptista da Silva, J.; Pinheiro Lima, V.; Brandão Pinto de Castro, J.; Miranda, H. (Biomedical Human Kinetics, 2016)
Study aim: To investigate the correlation between anthropometric parameters, Sargent jump test, core muscles endurance and agility performance versus specific tests with and without a ball in female Brazilian field hockey athletes. Material and methods: Nine professional female field hockey players (age: 27.4 ± 2.5 years) participated in this study. Body height, body weight, body fat percentage, Sargent jump test (SJT), shuttle run agility test (SR), core muscular endurance tests and sport-specific tests - repeated sprint ability test (RSA) and repeated sprint ability with the ball (RSAB) - were assessed in a randomized order. Results: A moderate correlation was noted between SR and RSAB (r = 0.58, p = 0.09) and RSA (r = 0.60, p = 0.08). In addition, a moderate correlation was noted between percentage of body fat with RSAB (r = 0.59, p = 0.09) and with RSA (r = 0.72, p = 0.08). The other variables showed slight agreement or no agreement. Conclusions: These results indicated that the SR could be implemented in training and evaluation programs of hockey athletes due to the correlation with specific tests. Thus, the percentage of body fat was the only anthropometric parameter that showed a correlation with the specific tests, revealing the importance of maintaining a proper percentage of body fat for better performance in hockey.